Evaluation Of Self-Care Management In Tuberculosis Patients: A Literature Review - Nursamsi; Syahrul Said; Yuliana Syam; Hamdana; Nadia Alfira; Edison Siringiringo (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2022)
Background : Self-care management is a response to signs and symptoms that occur in a person, so it always involves evaluating changes both physically and emotionally. These changes are caused by reactions to illness, medication, or the environment. Special care is taken for signs and symptoms of chronic disease. Objective : It is hoped that this article can evaluate the factors of self care management in patients with chronic diseases, see the effect of self care management on treatment, healing and prevention of relapse. Methods : search through PubMed, Google Scholar, ProQuest, and Wiley with the Critical Appraisal Skills Program/CASP guidelines. Result : 5 articles were searched in this discussion. In this article 12 indicators of self-care management are evaluated which are frequently used as instruments, extracted and tabulated. These factors include communication with staff, perceptions of self-care, level of trust, social support, coping behaviors, living habits, access to health services, nutrition and diet, medications, physical activity, and awareness to seek treatment. Conclusion : Appropriate and relevant evaluation of self-management skills and abilities is essential not only in gathering baseline data but also in testing interventions. The results of this study provide researchers with a new and better understanding and a range of choices for self-care. Keywords: Self-care management, Chronic disease, Instruments, Literature Review